Vitamin C, Phenolic Compounds and Antioxidant Capacity of Broccoli Florets Grown under Different Nitrogen Treatments Combined with Selenium - Peñas Elena; Zielińska Danuta; Gulewicz Piotr; Zieliński Henryk; Frias Juana (Polish Journal of Food and Nutrition Sciences)
Broccoli consumption is rising worldwide and fertilization is a tool to increase its production. However, little is known about the effect of mineral supplementation to the soil on the bioactive compounds. Therefore, the aim of this investigation was to analyze the content of vitamin C, total phenolic compounds and the antioxidant capacity of broccoli florets cultivated under different nitrogen (N) conditions in combination with selenium (IV and VI). Greenhouse experiments were conducted in broccoli grown in commercial soil treated with different N sources [(NH4)2SO4, NaNO3, NH4NO3 or CO(NH2)2 at 160 kg N/ha]. In addition, selenium (Se) salts [Na2SeO3 (Se IV) or Na2SeO4 (Se VI) at 10 and 20 kg Se/ha] were applied. There were no evidences of the influence of N treatment on vitamin C content whilst Se (IV or VI) uptake led to a significant reduction of this vitamin in broccoli florets, irrespective of the N source. In contrast, total phenolics content and antioxidant capacity underwent a significant increment under N application. However, their combination with Se salts modified total phenolic content and antioxidant capacities in broccoli florets depending on N source and Se doses. Among all the experimental trials, application of NH4NO3 combined with 10 g Se (IV)/ha was the elective treatment strategy to produce broccoli florets with higher content of phenolic compounds and antioxidant capacity and, therefore, enhanced functionality.